Lymphocytic mitochondrial aconitase activity is reduced in Alzheimer's disease and mild cognitive impairment - Mangialasche, Francesca; Baglioni, Mauro; Cecchetti, Roberta; Kivipelto, Miia; Ruggiero, Carmelinda; Piobbico, Danilo; Kussmaul, Lothar; Monastero, Roberto; Brancorsini, Stefano; Mecocci, Patrizia (Journal of Alzheimer's disease, 2015)
Specific mechanisms behind the role of oxidative/nitrosative stress and mitochondrial dysfunction in Alzheimer's disease (AD) pathogenesis remain elusive. Mitochondrial aconitase (ACO2) is a Krebs cycle enzyme sensitive to free radical-mediated damage. We assessed activity and expression of ACO2 extracted from blood lymphocytes of subjects with AD, mild cognitive impairment (MCI), older adults with normal cognition (OCN, age ≥65 years), and younger adults with normal cognition (YCN, age <65 years). Plasma levels and activities of antioxidants were also measured. Blood samples were collected from 28 subjects with AD, 22 with MCI, 21 OCN, and 19 YCN. ACO2 activity was evaluated in a subsample before and after in vitro exposure to free radicals. ACO2 activity was significantly lower in AD and MCI cases than controls: ACO2 median activity was 0.64 ± 0.21 U/mg protein for AD, 0.93 ± 0.28 U/mg protein for MCI, 1.17 ± 0.78 U/mg protein for OCN subjects, and 1.23 ± 0.43 U/mg protein for YCN individuals. In subjects with AD and MCI, ACO2 expression was lower than OCN subjects, and ACO2 activity correlated with vitamin E plasma levels (rho: 0.64, p < 0.001) and Mini-Mental State Examination total score (rho: 0.82, p < 0.001). Furthermore, free radicals exposure reduced ACO2 activity more in individuals with AD than in OCN subjects. Our results suggest that ACO2 activity is reduced in peripheral lymphocytes of subjects with AD and MCI and correlates with antioxidant protection. Further studies are warranted to verify the role of ACO2 in AD pathogenesis and its importance as a marker of AD progression.